Manajemen Isu Humas UPT PLN Madiun terkait Pemadaman Listrik Akibat Penerbangan Layang-Layang - Abigail Fedora Ondine; Regina Prima Cahyani Wisaksono; Afifah Yonni Febriana (Institut Nalanda, 2024)
Issue management is a management process within a company that aims to control the image that is an asset of a company. Public relations has an important role in carrying out issue management. The purpose of this research is to explain how the public relations of the Transmission Implementation Unit (UPT) of PT Perusahaan Listrik Negara (PLN) (Persero) Madiun in issue management related to kite flights causing power outages. This research uses descriptive qualitative research with in-depth interview techniques and a literature study. The theory involved in this research is the Five Stages of Issue Management Theory which resulted in the following research: 1) The Issue Identification Stage with Focus Group Discussion (FGD) and blusukan communication, 2) The Issue Analysis Stage found the cause of the issue, namely the community flying kites around transmission assets and the tradition of kite flights on holidays, 3) The Issue Change Strategy Selection Stage is an adaptive strategy, 4) The Issue Action Programming Stage is carried out by socialization involving opinion leaders, 5) The Results Evaluation Stage by monitoring the number of cases.